2013
DOI: 10.1002/2013ja018796
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ground and satellite observations of discrete auroral arcs, substorm aurora, and Alfvénic aurora with FAST and THEMIS GBO

Abstract: [1] Three distinct types of aurora are observed during separate events, using simultaneous measurements on the ground with all sky imagers from the THEMIS Ground-Based Observatories and in situ with the FAST auroral satellite. The three cases show discrete stable arcs, substorm aurora, and Alfvénic aurora. The field-aligned current structure associated with each type of aurora is shown to agree with contemporary auroral models. Inverted-V type aurora with electron energy peaks of 1-10 keV are observed, and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Discrete auroras sometimes show highly structured shapes whose scale sizes are ∼1 km or less [498], [499], [500]. Such thin arcs often behave more dynamically (i.e., not quasistatic), some of which is closely related to time-varying magnetic field-aligned electric fields associated with dispersive Alfvén waves [501], [502], [503], [504]. Details of the smallscale dynamic discrete aurora can be found in the review of Kataoka et al [505].…”
Section: A Discrete Aurorasmentioning
confidence: 99%
“…Discrete auroras sometimes show highly structured shapes whose scale sizes are ∼1 km or less [498], [499], [500]. Such thin arcs often behave more dynamically (i.e., not quasistatic), some of which is closely related to time-varying magnetic field-aligned electric fields associated with dispersive Alfvén waves [501], [502], [503], [504]. Details of the smallscale dynamic discrete aurora can be found in the review of Kataoka et al [505].…”
Section: A Discrete Aurorasmentioning
confidence: 99%
“…The visible aurora is caused by precipitating electrons with~1-10 keV energy (Colpitts et al, 2013;Tanskanen et al, 1981). Precipitating electron population can contain a high-energy tail of electrons of primary energies ranging from 10 to 100 keV that cause X-ray emissions (Brown, 1966).…”
Section: Sivadas Et Almentioning
confidence: 99%
“…It is in general difficult to distinguish between the Inverted V/monoenergetic and Alfvénic/broadband precipitation by observing the discrete aurora alone. For example, Colpitts et al [2013] observed Alfvénic aurora intermittently and perhaps simultaneously with inverted V aurora during an event of continuous substorm activity. They described the aurora as extremely dynamic changing on timescales of seconds with bright spots and arcs that were not as elongated in the east-west direction as during typical inverted V events.…”
Section: Controlling Parametersmentioning
confidence: 99%